Systematic and historical biogeography of the Bryconidae (Ostariophysi: Characiformes) suggesting a new rearrangement of its genera and an old origin of Mesoamerican ichthyofauna - Abe, Kelly T. [UNESP]; Mariguela, Tatiane C. [UNESP]; Avelino, Gleisy S. [UNESP]; Foresti, Fausto [UNESP]; Oliveira, Claudio [UNESP] (Biomed Central Ltd., 2014)
Background: Recent molecular hypotheses suggest that some traditional suprageneric taxa of Characiformes require revision, as they may not constitute monophyletic groups. This is the case for the Bryconidae. Various studies have proposed that this family (considered a subfamily by some authors) may be composed of different genera. However, until now, no phylogenetic study of all putative genera has been conducted.Results: In the present study, we analyzed 27 species (46 specimens) of all currently recognized genera of the Bryconidae (ingroup) and 208 species representing all other families and most genera of the Characiformes (outgroup). Five genes were sequenced: 16SrRNA, Cytochrome b, recombination activating gene 1 and 2 and myosin heavy chain 6 cardiac muscle. The final matrix contained 4699 bp and was analyzed by maximum likelihood, maximum parsimony and Bayesian analyses. The results show that the Bryconidae, composed of Brycon, Chilobrycon, Henochilus and Salminus, is monophyletic and is the sister group of Gasteropelecidae + Triportheidae. However, the genus Brycon is polyphyletic. Fossil studies suggest that the family originated approximately 47 million years ago (Ma) and that one of the two main lineages persisted only in trans-Andean rivers, including Central American rivers, suggesting a much older origin of Mesoamerican ichthyofauna than previously accepted.Conclusion: Bryconidae is composed by five main clades, including the genera Brycon, Chilobrycon, Henochilus and Salminus, but a taxonomic review of these groups is needed. Our results point to a possible ancient invasion of Central America, dating about 20.3 +/- 5.0 Ma (late Oligocene - early Miocene), to explain the occurrence of Brycon in Central America.
Keywords: Characiformes; Bryconidae; Evolution; Phylogeny; Systematics